2020
DOI: 10.1163/15685381-20191206
|View full text |Cite
|
Sign up to set email alerts
|

Testicular melanization in anuran species: ontogeny and sexual maturity

Abstract: Testicular melanization in anurans may be absent or present with different degrees of intensity. When present, the color is due to the concentration of melanocytes in external (surface) and interstitial tissue. The function of this coloration is not fully known and we ask if melanization during testicular development, in species with highly pigmented testes in adults, is correlated with germ cells maturation. To do so, we selected four anuran species with highly pigmented testes. Species differed in the amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Although ontogenetic variation in testis pigmentation is common, individual variation among adults is rare, and, prior to L. bilsa ( Vigle et al 2020 ), unilateral melanization in dendrobatoids had only been documented for Colostethus panamansis (Dunn, 1933) by Grant (2004) . Golberg et al (2020) found that testicular melanization and germ cell differentiation proceed in parallel in four anuran species, but the significance of intra-individual variation is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although ontogenetic variation in testis pigmentation is common, individual variation among adults is rare, and, prior to L. bilsa ( Vigle et al 2020 ), unilateral melanization in dendrobatoids had only been documented for Colostethus panamansis (Dunn, 1933) by Grant (2004) . Golberg et al (2020) found that testicular melanization and germ cell differentiation proceed in parallel in four anuran species, but the significance of intra-individual variation is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The study of these distribution patterns will likely result in more characters. Goldberg et al (2019) described ontogenetic variation associated with sexual maturation in testes coloration. All specimens studied by us are sexually mature adult males.…”
Section: Methodsmentioning
confidence: 99%